One good thing [large type] - Hunter, Georgia, 1978- (Random House Large Print, 2025)
"1941, Italy. Lili and Esti have been best friends since meeting at the university in Ferrara; when Esti gives birth to the adorable Theo, they become as close as sisters. But when Germany invades northern Italy, they will soon find themselves in occupied territory. Esti, always the fiercer of the two, convinces Lili to flee to a convent in Florence, where they'll be responsible for guarding war orphans and forging identification papers with the Resistance in the dead of night. When a brutal gang descends on the convent, a critically wounded Esti asks Lili to take a much bigger step: Go on the run with Theo. Protect him while Esti can't. Terrified to travel without her brave friend, Lili sets out on a harrowing journey through the bombed-out villages and cities of Italy, doing everything she can to keep Theo safe. A tale of friendship, motherhood, survival, and unexpected romance, in One Good Thing Lili will learn how love for another person can be a reason to stay alive"--